The Value of ADAMTS13 in Predicting Clinical Outcomes in Patients With Acute Ischemic Stroke Receiving Thrombolysis - Su, Ya; Chen, Xin; Ye, Xiaofei; Sun, Haiyan; Wu, Fei; Dong, Qiang; Cheng, Xin; Wu, Danhong (Frontiers in Neurology, 2020)
Objective: To determine the association between baseline ADAMTS13 (a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13) antigen level and 90-days clinical outcome in patients with acute ischemic stroke (AIS) receiving recombinant tissue plasminogen activator (rt-PA) thrombolysis. Methods: AIS patients receiving rt-PA thrombolytic therapy from Huashan Hospital and Fifth People's Hospital of Shanghai, China in 2014–2017 were consecutively enrolled. Blood samples for ADAMTS13 tests were drawn before intravenous rt-PA administration. The primary outcome was defined as the poor functional outcome of modified Rankin Scale (mRS) >2 at 90-days follow-up. Secondary outcome was hemorrhagic transformation after rt-PA therapy. Moreover, for AIS patients with large vessel occlusion from Huashan Hospital, the association between baseline ADAMTS13 level and cerebral collateral flow was also assessed. Results: A total of 163 AIS patients (median age 66.2 years, 63.8% male) were included. Baseline ADAMTS13 level was marginally decreased in patients with 90-days mRS >2 than in those with mRS ≤ 2 (mean ± SD, 1458.4 ± 323.3 vs. 1578.3 ± 395.4 ng/mL, p = 0.046). However, no difference of ADAMTS13 level was found after adjusting for age, history of atrial fibrillation, glycemia, baseline NIHSS score and TOAST classification (p = 0.43). We found no difference in ADAMTS13 level between patients with parenchymal hemorrhage after rt-PA therapy and those without (p = 0.44). Among 66 patients with large vessel occlusion, there was also no association between ADAMTS13 level and cerebral collateral flow in multivariable analyses. Conclusion: In our cohort, blood ADAMTS13 antigen level before rt-PA therapy could not be used as an independent biomarker in predicting clinical outcomes of AIS patients at 90 days.